Cultural Diplomacy of Kosovo after the Declaration of Independence - Saliu, Hasan; Llunji, Venera (Information & Media, 2022)
The article analyzes a segment of the cultural diplomacy of non-state actors of Kosovo who have communicated with foreign audiences through the international media in the period after the country’s declaration of independence in 2008. Analyzing the content of media coverage for non-state actors, the article examines the given messages of these actors in some powerful international media, which relate to the possibility of increasing the international image of the new country. The article finds that Kosovar non-state actors have continuously communicated with the global and regional public because it has been impossible for state actors to convey any positive message to the latter. The article, moreover, shows that Kosovar famous athletes and artists or world champions represent the soft power of Kosovo, because they have found enough space to be exposed in the international media. A significant feature of cultural diplomacy in the case of Kosovo is that the presence of hundreds and thousands of foreign peacekeepers in a country with as much security as other Balkan countries is also seen as an opportunity to influence the country’s international image.